2022
DOI: 10.1186/s12891-022-05831-7
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic accuracy of the Ottawa ankle rule to exclude fractures in acute ankle injuries in adults: a systematic review and meta-analysis

Abstract: Background Ankle traumas are common presenting injuries to emergency departments in Australia and worldwide. The Ottawa Ankle Rules (OAR) are a clinical decision tool to exclude ankle fractures, thereby precluding the need for radiographic imaging in patients with acute ankle injury. Previous studies support the OAR as an accurate means of excluding ankle and midfoot fractures, but have included a paediatric population, report both the ankle and mid-foot, or are greater than 5 years old. This s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 33 publications
1
10
0
1
Order By: Relevance
“…By minimizing unnecessary radiography, this clinical tool streamlines the diagnostic process and facilitates more efficient use of emergency department resources. [13,14] However, the limitations of the OAR must be recognized. Specifically, given the risk of overlooking certain fracture types, a holistic approach that incorporates clinical evaluation and patient history is essential.…”
Section: Discussionmentioning
confidence: 99%
“…By minimizing unnecessary radiography, this clinical tool streamlines the diagnostic process and facilitates more efficient use of emergency department resources. [13,14] However, the limitations of the OAR must be recognized. Specifically, given the risk of overlooking certain fracture types, a holistic approach that incorporates clinical evaluation and patient history is essential.…”
Section: Discussionmentioning
confidence: 99%
“…2 It is crucial to emphasize that the OAR is primarily applied in acute settings assessments generally conducted within 7 to 10 days of injury. 6,9,10,11 Systematic reviews reported high sensitivities ranging from 90% to 100% but with varying specificities (ranging from 10% to 80%) in the adult population. 4,6,9,15,16 Bachmann et al hypothesised that the accuracy of the OAR may vary due to differences in the assessors' clinical skills, experience in detecting and interpreting the findings, and the timing of assessments.…”
Section: Discussionmentioning
confidence: 99%
“…6,9,10,11 Systematic reviews reported high sensitivities ranging from 90% to 100% but with varying specificities (ranging from 10% to 80%) in the adult population. 4,6,9,15,16 Bachmann et al hypothesised that the accuracy of the OAR may vary due to differences in the assessors' clinical skills, experience in detecting and interpreting the findings, and the timing of assessments. 16 A delay in the assessment of the injury was also addressed as one of the influencing factors of the accuracy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ao exame físico, a entorse de tornozelo pode apresentar edema e equimose e é importante avaliar se existem outras lesões associadas como, por exemplo, fraturas. As regras do tornozelo de Ottawa (OAR) são uma ferramenta de decisão clínica que pode ser utilizada para excluir fraturas de tornozelo durante o exame físico, afastando a necessidade de radiografias em pacientes com lesão aguda do tornozelo (GOMES et al, 2022). Além disso, é importante verificar se há dor na inversão passiva suave e na eversão do tornozelo, visto que a dor aumenta com a inversão forçada do tornozelo nos casos de entorses laterais, enquanto a dor de uma entorse medial é acentuada durante a eversão do tornozelo (RENSTRÖM et al, 1999).…”
Section: Lesões No Tornozelounclassified